Vragen des Tijds. (Haarlem : H.D. Tjeenk Willink, 1880)
Vrijzinnige Werkmansbibliotheek Leren Vereert
Redactie: H. Goeman Borgesius, W. Heineken, S. Van Houten, A. Kerdijk, B.H. Pekelharing, J.W. Straatman, J. D. Veegens, F. Domela Nieuwenhuis, P. Van Geer
Nederlands
Periodiek